FORMATION OF LUMINESCENT NANOCRYSTALLINE SILICON FILMS FROM A-SI:H BY USING RAPID THERMAL ANNEALING AND WET CHEMICAL ETCHING - Taurbayev, Ye. T.; Dihanbayev, K. K.; Nikulin, V. E.; Svanbayev, E. A.; Taurbayev, T. I.; Timoshenko, Yu.; Maslova, N. E.; Gonchar, K. A. (Хабаршы. Физика сериясы, 2009)
Nanocrystalline silicon films, which exhibit efficient photoluminescence, were formed from amorphous films of hydrogenated silicon subjected to rapid thermal annealing and stain etching in hydrofluoric acid based solutions. The samples were investigated by means of scanning and transmission electron microscopy, optical spectroscopy of reflection, Raman scattering and photoluminescence methods, which revealed the nanocrystalline structure and excellent optical quality of the formed nc-Si films.